GROWING Plasmodium berghei ANKA (PbA) FROM FROZEN AND FRESH DONORS: A COMPARATIVE STUDY - Putu Indah Budi Apsari; Ni Wayan Winianti; Dewa Ayu Agus Sri Laksemi (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: Plasmodium berghei is a rodent malaria parasite that infects mice and rats that mimics Plasmodium falciparum. It has a problem with standardized growing time and reaching high percentages of parasitemia, which allows optimum conditions in antimalarial research.Objective: This study aimed to analyze different outcomes from growing P. berghei ANKA (PbA) from frozen compared with fresh donors.Methods: The study involved 20 mice, with 10 infected using fresh and 10 using frozen P. berghei inocula. Blood smears were prepared daily for 7 days, fixed with methanol, stained with Giemsa, and examined every 24 hours at 1000Ã— magnification. Parasitemia was calculated as infected erythrocytes per 1000 cells, recorded from initial parasite detection, and analyzed using a t-test.Results: Parasite growth in mice inoculated with fresh and frozen P. berghei blood was monitored through parasitemia levels over 7 days. In the fresh blood group, parasites appeared on day 2 (0.8%) and increased steadily to 11.3% by day 7. In contrast, parasites in the frozen blood group were first detected on day 3 at a low level (0.1%) and rose gradually to 5.0% on day 7.Conclusions:Â In conclusion, this finding indicates the fresh blood contains more active and viable parasites, enabling them to rapidly replicate within the mice's bodies.